Analisa Kebutuhan Dan Ketersediaan Air Bersih Untuk Masyarakat Kecamatan Medan Deli di Kota Medan - dimas farqa ghurril; Butar-Butar, Laurensia; Dicky, Muhammad; Rahman, Muhammad Rizki Aulia; Ananda, Riska; Mulyana, Rachmat; Wardana, Novrizaldi (Civil Engineering Department, Faculty of Engineering, Universitas Swadaya Gunung Jati, 2025)
Clean water is a basic necessity crucial for life, health, and socio-economic development. In Medan Deli District, although water sources are still available, challenges arise in distribution, technical losses, and processing and management capacity. This study aims to analyze the projection of clean water needs and availability in the next 10, 30, and 50 years, taking into account population growth, service coverage, and the capacity of PDAM Tirta Deli. The methods used include literature studies, secondary data collection, and calculations of domestic and non-domestic water needs based on the Directorate General of Human Settlements standards. The projection results show an increase in population from 193,196 people (2025) to 239,426 people (2075), and an increase in total water needs from 289.57 liters/second to 358.86 liters/second, including 15% technical losses. The PDAM's installed capacity of 400 liters/second is nominally sufficient, but its effectiveness may decrease without improvements to the distribution and management system. This study recommends long-term planning, infrastructure improvements, and attention to climate change and consumption patterns to ensure the sustainability of clean water supplies in the future. Key recommendations include investment in water leakage reduction technologies and strengthening the institutional capacity of water utilities (PDAMs) to improve the efficiency of the clean water supply system.